Patterns of orofacial clefts and associated risk factors in Pakistan: An institutional experience - Hamza Sadiq; Rafia Ijaz; Ayisha Ayub (Wolters Kluwer Medknow Publications, 2022)
Background: Orofacial clefts (OFCs) are one of the most common congenital anomalies worldwide. The purpose of the present study is to identify the incidence of different types of OFCs and the presence of known risk factors among cleft cases in the Pakistani population. Patients and Methods: A retrospective study was conducted at a comprehensive cleft care center, and data were collected from patient files from December 2018 to July 2021. Only cases of cleft lip and/or cleft palate (CL/P) that presented to center were included. SPSS was used for data analysis, and risk factors associated with OFCs were identified. Results: The study included 1269 patients with CL/P. Of the total, 677 (53.3%) patients had cleft lip with cleft palate, 211 (16.6%) had cleft lip only, and 365 (28.7%) had cleft palate only. Bilateral complete cleft lip and palate (n = 276) was most common among the participants followed by midline incomplete cleft palate (n = 215). One hundred and six (8.3%) of the cases were syndromic, and among the remaining nonsyndromic cases, 240 (18.9%) had other associated anomalies. Chi-square tests revealed the following risk factors for CL/P: consanguinity among the parents (P < 0.001), a complication during pregnancy (P < 0.001), medication use during pregnancy (P < 0.001), maternal smoking or exposure to smoking (P = 0.002), history of miscarriage (P = 0.02), and positive family history (P < 0.001). Logistic regression analysis for these factors showed maternal smoking (odds ratio [OR]: 1.99), consanguineous marriage (OR: 1.89), complication during pregnancy (OR: 1.98), and positive history of cleft (OR: 1.9) to be increasing the odds of cleft development. Conclusion: While previous studies have shown many environmental factors to be associated with development of OFCs in the child, the present study provides a quantitative estimate of the risk posed by each individual factor in the Pakistani population.